Promotion of angiogenesis and suppression of inflammatory response in skin wound healing using exosome-loaded collagen sponge - Zhang, Siqi; Lu, Xugang; Chen, Jun; Xiong, Shibing; Cui, Yifan; Wang, Simeng; Yue, Chongxia; Han, Qianqian; Yang, Bangcheng (Frontiers in Immunology, 2024)
Effectively promoting skin wound healing remains a significant challenge in the medical field. Although stem cell-derived exosomes show potential in tissue regeneration, their local delivery and sustained release face challenges. To address these issues, we developed a collagen sponge based on type I and recombinant humanized type III collagen. Our study confirmed that exosomes were successfully loaded onto the sponge (sponge-Exo) and the sponge-Exo gradually released exosomes into the local milieu. The sponge-Exo played a crucial role in promoting the transition of macrophages from an inflammatory M1 phenotype to a regenerative M2 phenotype. Moreover, it enhanced the migration and proliferation of HDFs and promoted angiogenesis in HUVECs. Additionally, our findings revealed that the sponge-Exo accelerated wound healing by suppressing inflammatory response and stimulating angiogenesis in a rat full-thickness skin wounds model. Next generation sequencing (NGS) was used to explore the underlying mechanism of wound healing, and the results showed that the miRNAs (hsa-miR-21-5p and hsa-miR-29a-5p) associated with wound healing in exosomes were significantly up-regulated. These results highlight the remarkable effects of sponge-Exo on macrophage transformation, cell migration, proliferation and angiogenesis, which provide a potential prospect for the application in the field of skin wound healing.